교양교육을 위한 대학의 핵심역량 개발 과정 연구 - 이병주(Lee, young-whan) (교양교육연구, 2019)
대학교육은 핵심역량을 중심으로 운영된 지 오래되었다. 핵심역량 중심의 교육은 목표와 성과 를 더욱 분명히 할 수 있게 해준다. 이런 점에서 핵심역량에 대한 학계의 관심은 매우 높은 실정 이다. 아울러 각 대학은 이러한 핵심역량 중심의 교육과정을 운영하기 위해, 각 대학의 특성에 적 합한 핵심역량을 개발하여 운영한다. 본 연구는 이때 요구되는 핵심역량의 개발과 설정에 관한 연구로서, 하나의 사례를 중심으로 살펴봄으로써 그 실제에 접근하고자 하였다. 핵심역량의 개발은 다양한 측면을 반영한다. 대내·외적인 환경과 사회적 변화 양상을 분석함 은 물론 교육 수요자의 요구와 현재 역량 정도를 반영한다. 아울러 대학의 인재상과 특성이 핵심 역량에 반영되도록 한다. 학내 구성원과 핵심역량 중심 교육과정 운영주체인 각 학과 및 부서간 의 협의 내용도 중요한 측면이다. 핵심역량은 이러한 과정을 통해 도출되며, 운영의 효율성을 높 이기 위해 명확하게 정의되어 교육과정에 반영된다. It’s been a long time that university education is operated focusing on core competence. Education of core competence have a good point which make clear goals and outcomes of education. In this sense, concern of academic world about core competence is very high. Furthermore each university research and development for characteristics to operate education courses focusing on core competence. This study is about setting and developing core competence which is interested in this field. This study want to approach actual examining by focusing one cases. Development of core competence reflects various components. It reflects circumstances internally and externally and changing complexion in society, and also education consumer’s needs, current capabilities. In addition core competence have to include the right people and characteristics. Each department and division that is subject of operates, is very important side. Core competence is derived from this process and to operational efficiency must to be defined and reflected in education courses. KCI Citation Count: 13